Association of hypothyroidism and polycystic ovarian syndrome: a study in a semi urban area - Ram Babu, M. V.; Vittal, D. Sai (International Journal of Advances in Medicine, 2019)
Background: Polycystic ovarian syndrome reported to be one of the most common endocrine disorders in the women of the reproductive age, causing oligoovulatory infertility. In many cases, apparently healthy looking women are being diagnosed with either subclinical or overt hypothyroidism after having the symptoms of PCOS. This study was done to analyse the association of PCOS and hypothyroidism in our geographical area. Methods: 50 women of reproductive ages between 18 to 45 years, who were diagnosed with PCOS, based on Rotterdam’s criteria, 2003 and 50 healthy women as controls, were included into the study. After taking the demographic details from all the patients, they were all subjected to ultrasound for the detection of the cysts. Blood was collected for various biochemical tests including the thyroid profile. Results: The mean age of all the patients in the study group was 23.6±7.2 compared to 27.1±4.6 of the healthy controls. The Body Mass Index amongst both the groups was 29.1±3.1 and 23.4±2.9 kg/m2 respectively. The levels of thyroid profile were significantly high among the study group with 58%, 54%, 68% as the number of patients with elevated T3, T4 and TSH values. The prevalence of subclinical hypothyroidism was 48.3%, while 51.7% of them had overt hypothyroidism. A higher BMI was found among the patients with PCOS and hypothyroidism. Conclusion: The prevalence of hypothyroidism among the PCOS patients is certainly on the rise accentuating its association with this endocrine disorder especially among the young adults.